ADAPTASI PENGUNGSI ERUPSI MERAPI 2010 TERHADAP PERMUKIMAN BARU - , Hesti Widayani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Merapi eruption that occurred in 2010 had buried some villages in the Yogyakarta Special Region (DIY) and destroyed thousands of houses. Furthermore, that region is set to be Disaster Prone Region III which is not recommended as residential area. Under these conditions, the people originally lived there, relocated to another place called the permanent residential. The settlement in permanent residential is row house, huddle with a narrow yard equipped with common facilities such as mosque, drainages, paving roads, communal cattle corral, warehouse and preschool. The situation is very different from the previous one belongs to the citizens. Meanwhile, the previous settlement comprises roomy houses, spacious grounds, and large distance between houses. Those differences insist the refugees to be able to adapt with the their new living environment. The purpose of this study is to conduct exploration in order to build the concept of adaptation made by the victims of Merapiâs eruption towards new settlements in Batur Permanent Residential and to find out the factors that influence the adaptation. This study is a qualitative study using the inductive logic thinking and phenomenological method. This method is trying to understand the meaning of events and its linkages with the people who are in that situation. Data analysis performed in this study is descriptive qualitative . The results and conclusions of this study can be illustrated in the concept of \"narimo kanyatan manggon ing papan relokasi\" (accept a reality to live in the permanent residential). This concept can be interpreted as an acceptance towards the loss of homes and properties due to Merapiâs eruption and the refugeesâs willingness to live in another place with all its limitations. Moreover, the narimo kanyatan (accept a reality) concept is the attitude of surrender to the God who created the Merapi and its accompanying impact. This concept is also defined that people did not just stand by and kept silent when met all of the changes that happened after the disaster, but they were struggling actively to adapt againts their new environment. Adaptations made by residents in the Batur Permanen Residential include adaptation to changes in the physical, social and economic which have been experienced in the new settlements. The main factor that influencing the refugeesâs adaptation is awareness and understanding of the reasons why they have to be relocated, which shape the attitude to accept the faced condition and gratitude for the post-disaster housing. While the external driving factors are the unity and similar feeling with other refugees in the Batur Permanent Residential, the housesâs arrangement which consider the impression of previous settlements, and the adequate facilities in the permanent residential.